Pengaruh Pendidikan Kesehatan Tentang Regurgitasi Terhadap Praktik Ibu Dalam Mencegah Dan Menangani Regurgitasi Pada Bayi (0-3 bulan) Di Kelurahan Pudakpayung Kota Semarang - Dina Eva Mellinda; Muhammad Hasib Ardani (Jurusan Keperawatan, Universitas Diponegoro, 2012)
Regurgitation is the return of a number of the undigested food from the stomach. Regurgitation occurs in most healthy babies aged 3 months. Although normal, the excessive regurgitation can lead to various complications that would interfere with the growth of the baby if not prevented and handle with the right way. The purposed of this study is to determine the effect of health education about regurgitation on mother practice to preventing and dealing regurgitation on babies (0-3 months) in the Kelurahan Pudak Payung. This research plan methode used quasi experimental approach with one group pre test - post test design. Data collection tools is a checklist that has been tested using the correlation coefficient biserial validity and reliability testing with KR techniques (Kuder Richardson)-20. Univariate analysis of the data showed that before the health education, practices to prevent either the percentage of 52% and good handling practices with percentages 56%, after health education, practices to prevent either the percentage of 72% and good handling practices with a percentage of 60%.Analysed of bivariate data using Paired T-Test. The results showed significant differences between the practices of mothers in preventing regurgitation before and after health education with p value 0.00< α 0.05 and there are significant differences between the practices of mothers in dealing with regurgitation before and after health education with p value 0.0< α 0.05. Information from this study can be expected by the mothers to practice prevention of regurgitation in the right way such as improving breastfeeding technique and help baby burp after the baby feeds and treatment of regurgitation in the right way such as help baby burp after the baby had regurgitation and tilting the entire body of the baby when the baby has regurgitation every time they care of their babies